The Mediating Role of Job Satisfaction in Relationship Between Top Management Support on Employee Performance - Kumaladewi, Sri Eka; Suyono, Joko; Elisabeth, Damarsari Ratnasahara (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The purpose of this study is to analyze the influence of top management support on employee performance, top management support on job satisfaction, and also to analyze the mediating role of job satisfaction. Design/methodology/approach: The sample in this study were 70 employes of regional drinking company owned by the regional government in East Java, Indonesia. Questionnaire was used to obtain the data and data analysis technique used was Partial Least Square (PLS). Findings: The results indicated that top management support influences employee performance, top management support influences job satisfaction, and job satisfaction is able to mediate the influence of top management support on employee performance. Research limitations/implications: This research is limited to doing regional drinking company owned by the regional government in East Java, Indonesia. For generalization so that further research can be carried out in different organizations or companies and in different regions (cities). Practical implications: The results of this research can be used as a reference to improve employee performance in regional drinking company owned by the regional government and similar industries. Originality/value: The results of the research show that among the variables of top management support and job satisfaction need to be implemented in regional drinking company owned by the regional government and similar industries.